Challenging Patriarchal Culture of Taliban Regime: A Woman Struggles in Qaderi’s Dancing in The Mosque - Astuti, Epata Puji; Abellya, Fernisya (Journal of Language and Literature, 2024)
Afghanistan, during the Taliban regime, has traditionally been shaped by patriarchal cultural norms and values that limit women’s rights and opportunities. Homeira Qaderi’s novel Dancing in The Mosque deals with the struggles and challenges faced by Afghan women, particularly in a patriarchal society that oppresses and limits their freedoms. The three objectives of this study are to describe the patriarchal culture of the Taliban Regime and its effects on women and the actions of the women characters to fight against the patriarchal. The researcher uses the library method to help analyze this research. The primary data of this research is a novel entitled Dancing in The Mosque by Homeira Qaderi (2020). The secondary data comprises books, various journals, and articles related to women’s struggles during the Taliban regime. The feminist approach is used to reveal the action of the women characters to fight against the patriarchal culture and the theory of patriarchy is used to reveal the impact of patriarchal culture on Afghan women. This study concludes that Afghan women challenge the patriarchal culture by speaking up through education and making petitions claiming their rights. Education empowers them with knowledge and skills, enables them to gain financial independence, and helps to challenge and change traditional gender roles and cultural norms that perpetuate inequality. Education also increases women’s self-esteem and confidence, which allows them to participate more actively in society and make decisions that impact their own lives and the lives of their families and communities.